Developing a Cantonese Version of Birmingham Cognitive Screen for Stroke Survivors in Hong Kong. (May 2018) - Kong, Anthony Pak-Hin; Chan, John; Lau, Johnny King-L.; Bickerton, Wai-Ling; Weekes, Brendan; Humphreys, Glyn
The Birmingham Cognitive Screen (BCoS) is a neuropsychological battery designed to assess impairment to a variety of cognitive domains including language in patients with brain injuries. Twenty-two stroke participants and 16 gender-, age-, and education-matched controls were recruited in Hong Kong. The stroke participants were administered HK-BCoS as well as standardized batteries of cognitive and language functions validated for the Cantonese-speaking population in Hong Kong, including the Cantonese version of the Western Aphasia Battery, Cantonese Mini-Mental State Examination, and the Hong Kong–Montreal Cognitive Assessment . Results showed that HK-BCoS demonstrated good concurrent validity with all standardized batteries. HK-BCoS could discriminate between cognitive impairments in stroke patients and normal participants. Furthermore, HK-BCoS was found to have excellent intrarater and interrater reliabilities, good test–retest reliability, and fair split-half reliability as judged according to international criteria. In sum, HK-BCoS is a valid and reliable tool for assessing cognitive processing in Cantonese speakers in Hong Kong.